PENGARUH PERSEPSI HARGA, KUALITAS PELAYANAN, DAN CITRA MEREK TERHADAP KEPUASAN TAMU DI THE MARGO HOTEL - Afraka Arga Wibowo; Chatarina Yunita (PT Naureen Digital Education, 2023)
This research analyzes the influence of price perception, service quality, and brand image on guest satisfaction at The Margo Hotel. Data was collected through a survey using a questionnaire given to guests who had stayed at the hotel. Multiple linear regression analysis was used to test the relationships between the variables under investigation. The results of the study indicate that price perception has a positive impact on guest satisfaction. The lower the perceived price, the higher the level of guest satisfaction. Service quality does not have a significant positive impact on guest satisfaction. Additionally, a strong and positive brand image contributes to guest satisfaction at The Margo Hotel. This research provides important insights for hotel management in enhancing guest satisfaction by considering factors such as price perception, service quality, and brand image. Strategies for improving guest satisfaction based on these findings can help the hotel strengthen its brand image and enhance the guest experience.